Islam and Online Piety in Bangladesh - Al-Zaman, Md. Sayeed (Universitas Ahmad Dahlan, 2020)
Due to various social advancements, Bangladesh has become more welcoming to digital technologies. Thus, a significant online community is flourishing here. Almost half of the countryâ€™s entire population uses the internet. The digital neighborhood is becoming larger the mediated interaction. What we now call online is nothing but a reflection of offline except its physicality. Like other social phenomena, religion and religious discourse is also a part of cyber society. Belief in cyberspace is often dubbed as â€œcyber-religionâ€. Debates on religion often harm the opposite group and contend faiths transform peace into communal animosity beyond cyberspace. Thus, society gets heated by hostile collective performances. In contemporary Bangladesh, online piety is an exclusive phenomenon that has considerable importance. By observing the dynamics of online religiosity, this paper focusing more on social media tries to present a concise overview of digital Islam(ism) and the social psychology of online Islamic piety in the context of Bangladesh.